Molecular Microbial Ecology of the Soil 1998
DOI: 10.1007/978-94-017-2321-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Rhizobium and Bradyrhizobium species as plant growth promoting rhizobacteria on non-legumes: Effect on radishes (Raphanus sativus L.)

Abstract: Bradyrhizobia and rhizobia are symbiotic bacterial partners forming nitrogen fixing nodules on legumes. These bacteria share characteristics with plant growth promoting rhizobacteria (PGPR). Nodule inducing bacteria, like other PGPR, are capable of colonizing the roots of non-legumes and produce phytohormones, siderophores and HeN. They also exhibit antagonistic effects towards many plant pathogenic fungi. The potential of nodule inducing bacteria to function as PGPR, was examined by using radish as a model pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
145
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 38 publications
5
145
0
16
Order By: Relevance
“…(Junier et al, 2009), as well as symbiotic N-fixing bacteria (Bradyrhizobium) (Stacey et al, 1995) or Herbaspirillum which is involved in endophytic N fixation (Elbeltagy et al, 2001;Franche et al, 2009). It should be noted that in addition to fixing N through legume symbiosis, Bradyrhizobium promotes plant growth of nonleguminous plants (Antoun et al, 1998). The functional microbiome also expressed genes that aligned to the free N-fixing Cyanobacteria (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…(Junier et al, 2009), as well as symbiotic N-fixing bacteria (Bradyrhizobium) (Stacey et al, 1995) or Herbaspirillum which is involved in endophytic N fixation (Elbeltagy et al, 2001;Franche et al, 2009). It should be noted that in addition to fixing N through legume symbiosis, Bradyrhizobium promotes plant growth of nonleguminous plants (Antoun et al, 1998). The functional microbiome also expressed genes that aligned to the free N-fixing Cyanobacteria (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that production of organic acids by PGPR contributes the conversion of insoluble form of P to soluble (H2 PO 4 , HPO 2 4 ) forms (Sundara et al, 2002;Richardson et al, 2009). PGPRs which enhance P solubilization have been isolated and their functions were studied in range of crops such as wheat, tomato and radish (Kim et al, 1998;Antoun et al, 1998;Singh and Kapoor, 1999;Kumar and Narula, 1999). In the case of other crops such as sugar cane, increase in brix has been reported as an indirect function of PGPR to control pathogen attack (Senthil et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This growth limiting behaviour may be observed due to excessive production of materials (IAA and similar substances) that are beneficial for plant growth at minor quantity (Antoun et al, 1998). In the same way, Alstrom and Burn (1989) have also reported for growth limiting effects on the growth of plants which is attributable due to the production of HCN at higher concentration.…”
Section: Discussionmentioning
confidence: 84%
“…As a result, plant growth promoting rhizobacteria (PGPR) with their growth promoting ability are spotlighted and are being applied widely to agricultural crops as this technology is quite suitable to increase plant growth and decrease the use of chemical inputs. Several mechanisms have also been reported by which PGPR can directly stimulate the growth of plants including (1) production of phytohormones like IAA, Gibberellin, Kinetin and Cytokinin (Noel et al, 1996;Antoun et al, 1998;Verma et al, 2001;Dey et al, 2004) and (2) enzymes generation that can alter growth and development of plants (Yang and Hoffman, 1984;Sharma et al, 2011). The production of growth promoting substances like gibberellins, cytokinins and auxins by inoculated bacteria have positive impact on plant growth and yield.…”
Section: Introductionmentioning
confidence: 99%